"ERZİNCAN OVASI`NIN BEŞERİ VE İKTİSADİ COĞRAFYASI" - HAYLİ, SELÇUK (Fırat Üniveristesi, 1995)
Erzincan Hain is situated in the upper Euphrate the East Anatolien Region and the foundries of Erzincan province. The plain surrounded by Otlukbeli in the northeast, Esence in the north, Munzur Mountains in the south and Karadağ in the west, is a tectonic river- basin about 570 km2. In this study, with the plain itself, the low parts of nearby mountainous areas have been included as well. Within this frame the research field is about 1628.5 km2. Erzincan Plain surrounded by "North Anatolien Fault" and the other faults evolved with it in the north and the southis quite active with earthquakes. Due to geographical status and geomorphologic features, apart from the usual climate characteristics of the East Anatolien Region, some climatic conditions have been seen. According to 61 years of observations, the average heat is 10.6 °C, and rainfall is 367 mm. yearly. On account of the vegetation having been ruined and lithological features, the montainous areas surrounding the plain have undergone excessive erosion and forest cover has been lissened. The most important stream crossing the plain in the middle and making drainage possible is Fırat (Karasu) river. In addition, Vasgirt (Işıkpınar), Çardaklı, Göyne and Akpınar (Girlevik) streams are important side branches. In this field of study including the whole of Erzincan central county and the county Üzümlü a part of wich is in the plain, ther are two cities (Erzincan and Üzümlü) 105 villages and 85 smaller settlements (mahalle, çiftlik, yayla). Constructions owing to the earthquakes in the styles of dwellings, the materials used and the forms of settlements, there have been outstanding changes. After the eartquake on 13 March 1992, the places of a great many number of villages have been changed. In Erzincan damaged badly in the city center, reconstruction studies have been continuing. Erzincan Plain has a high agricultural potantial. In the policultural field agriculture system carried out excessively, cereals, beans and sugar beets are grown the most. Growing various vegetable and fruits (especially grape) is also important. Apart from cultivation activities, sheep breeding and bee keeping are other economical activities. The area has a high potantial in transportation, trade and tourism.
Human and economical geography of Erzincan Plain
Keywords: Coğrafya; Geography